Reconstruction of ice sheet retreat after the Last Glacial maximum in Storfjorden, southern Svalbard - Nielsen, Tove; Rasmussen, Tine Lander (Marine Geology, 2018)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Source at: http://doi.org/10.1016/j.margeo.2017.12.003 Storfjorden is a large north-south trending sound located in the southern part of Svalbard in the northwestern Barents Sea. Presently, several glaciers drain into the northern and western part of Storfjorden. Our study area covers the southern part of the sound, which is divided by a north-south striking basement ridge (the ‘Mid-ridge’) into a narrow western trough (‘Little-Storfjorden’) and a broader eastern trough (‘Storfjorden’). In the latter, three grounding-zone wedges (GZWs) were discovered in 2005 showing evidence of former grounded ice. Here we confirm the existence and map the extent of the GZWs and reconstruct the pattern and timing of ice retreat in Storfjorden during the deglaciation. The study is based on high-resolution seismic and shallow-acoustic profiles and swath bathymetry, combined with information of lithology and radiocarbon dates from sediment cores. The results show that the three GZWs stretch across the fjord, and that all three are located south of higher basement areas that were upstream of the GZWs and which acted as pinning points during ice retreat. The Mid-ridge imposed a lateral drag to the ice, resulting in an uneven ice retreat across the fjord. Outside of the GZWs only a thin cover of glacial deposits was found. The cores were taken in vicinity of the GZWs and all reached till deposits overlain by glacimarine or hemipelagic sediments, enabling dating of the GZWs. Altogether we find that the fjord and basement topography played an important role in the ice retreat. AMS-14C dates show that the formation of the three GZWs correlate with three well-known atmospheric warming phases (start of Bølling interstadial, Allerød interstadial and Holocene interglacial, respectively) associated with inflows of warm Atlantic water, indicating a strong ocean/climate control on the deglaciation of Storfjorden.